Valorização dos compostos terpênicos via catálise por ácidos: Esterificação e eterificação do canfeno isomerização do óxido de alfa-pineno - Augusto Luis Pereira de Meireles (2013)
This study aimed the development of efficient, environmentally clean and selective heterogeneous processes for the catalytic transformation of natural-renewable substrates easily available from essential oils. In order to obtain fine chemicals with high added value and commercial interest, this may replace current technologies for more advanced ones.Silica supported H3PW12O40 (PW), the strongest heteropoly acid in the Keggin series, is an active and environmentally friendly catalyst for the liquid-phase esterification of camphene with C2¡VC6 fatty acids under heterogeneous conditions. The developed efficient and clean method provides various fragrance isobornyl carboxylates in virtually 100% selectivity and 80¡V90% GC yields. The reactions are equilibrium-limited and occur under mild conditions with a catalyst turnover number of up to 3000. The use of apolar hydrocarbon solvents permits to avoid PW leaching and to recover the catalyst by facile filtration or centrifugation. The catalyst can be reused several times without loss of activity and selectivity. The liquid-phase eterification of camphene was studied in the presence of heteropoly acid catalysts in some alcoholic solvents in homogeneous and heterogeneous systems. Among the catalysts were bulk tungstophosphoric acid H3PW12O40 and its acidic Cs salt Cs2,5H0,5PW12O40 (CsPW). The reaction gave various fragrance isobornyl alcoxylates in 80-100% selectivity and 60-76% GC yields. The reactions are equilibrium-limited and occur with a catalyst turnover number of up to 1300. This simple catalytic method represents economically attractive route to industrially important compounds starting from bio-renewable substrates easily available from essential oils.Iron-modified mesoporous silicates (Fe-MCM) were prepared through a direct hydrothermal method and characterized by N2 adsorption-desorption, XRD, Mossbauer spectroscopy and SEM-EDS techniques. Characterizations suggest that most of the introduced iron species present on the material surface rather than in the silicate framework. Besides the framework included Fe3+ ions (0.2¡V0.3 wt.%), both materials contain only the trivalent iron (as hematite). The materials were shown to be efficient heterogeneous catalysts for the transformation of Ñ-pinene oxide in various value-added fragrance compounds, with the product distribution being remarkably dependent on the solventnature. The method represents one of the few examples of the selective synthesis of other than campholenic aldehyde compounds from Ñ-pinene oxide through its acid-catalyzed isomerization.